29,000,000,000,000: A detailed look at the Fed's bailout by funding facility and recipient - James Felkerson (Levy Economics Institute of Bard College, 2011)
There have been a number of estimates of the total amount of funding provided by the Federal Reserve to bail out the financial system. For example, Bloomberg recently claimed that the cumulative commitment by the Fed (this includes asset purchases plus lending) was 7.77 trillion. As part of the Ford Foundation project 'A Research and Policy Dialogue Project on Improving Governance of the Government Safety Net in Financial Crisis', Nicola Matthews and James Felkerson have undertaken an examination of the data on the Fed's bailout of the financial system - the most comprehensive investigation of the raw data to date. This working paper is the first in a series that will report the results of this investigation. The extraordinary scope and magnitude of the recent financial crisis of 2007-09 required an extraordinary response by the Fed in the fulfillment of its lender-of-last-resort function. The purpose of this paper is to provide a descriptive account of the Fed's response to the recent financial crisis. It begins with a brief summary of the methodology, then outlines the unconventional facilities and programs aimed at stabilizing the existing financial structure. The paper concludes with a summary of the scope and magnitude of the Fed's crisis response. The bottom line: a Federal Reserve bailout commitment in excess of 29 trillion.
Keywords: E58; E65; G01; 330; global financial crisis; fed bailout; lender of last resort; term auction facility; central bank liquidity swaps; single tranche open market operation; term securities lending facility and term options program; maiden lane; primary dealer credit facility; asset-backed commercial paper money market mutual fund liquidity facility; commercial paper funding facility; term asset-backed securities loan facility; agency mortgage-backed security purchase program; AIG revolving credit facility; AIG securities borrowing facility